2005
DOI: 10.1097/01.mao.0000187236.10842.d5
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Conducted Sound: Physiological and Clinical Aspects

Abstract: Five factors contributing to bone conduction hearing have been identified: 1) sound radiated into the external ear canal, 2) middle ear ossicle inertia, 3) inertia of the cochlear fluids, 4) compression of the cochlear walls, and 5) pressure transmission from the cerebrospinal fluid. Of these five, inertia of the cochlear fluid seems most important. Bone conduction sound is believed to reflect the true cochlear function; however, certain conditions such as middle ear diseases can affect bone conduction sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
301
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 357 publications
(316 citation statements)
references
References 72 publications
6
301
0
9
Order By: Relevance
“…At the higher frequencies, above 2 kHz, there was a general trend of lower ECSP occlusion effect values when compared with the threshold based occlusion effect for all three stimulation positions (Table 3). This was due to the reduction of ECSP caused by the occlusion at higher frequencies, while perception of BC sound was not influenced by occlusion (and therefore insensitive to the decrease in ECSP) due to the contribution of other BC pathways to stimulus perception (Stenfelt and Goode, 2005b;Stenfelt and Reinfeldt, 2007).…”
Section: Occlusion Effects At Different Stimulation Positionsmentioning
confidence: 95%
See 2 more Smart Citations
“…At the higher frequencies, above 2 kHz, there was a general trend of lower ECSP occlusion effect values when compared with the threshold based occlusion effect for all three stimulation positions (Table 3). This was due to the reduction of ECSP caused by the occlusion at higher frequencies, while perception of BC sound was not influenced by occlusion (and therefore insensitive to the decrease in ECSP) due to the contribution of other BC pathways to stimulus perception (Stenfelt and Goode, 2005b;Stenfelt and Reinfeldt, 2007).…”
Section: Occlusion Effects At Different Stimulation Positionsmentioning
confidence: 95%
“…It has been shown that the ossicles' vibration is higher when the stimulation is in line with the lowfrequency vibration direction of the ossicles than for the perpendicular directions (Stenfelt et al, 2002). Also, it has been suggested that the ossicles can contribute to the perceived BC sound in the 2 to 3 kHz frequency range (Stenfelt and Goode, 2005b;Stenfelt, 2006). Consequently, the difference seen at 3 kHz, and to some extent at 2 kHz, may be due to the contribution of the ossicles when the stimulation was at the ipsilateral mastoid compared to less or nonexistent ossicle contribution when the stimulation was at the other positions.…”
Section: Difference Between Ear-canal Sound Pressure and Hearing Thrementioning
confidence: 99%
See 1 more Smart Citation
“…A sound transmitted by bone conduction travels via different pathways after becoming a vibration of the skull bone or soft tissues. Five pathways have been identified as the most important for BC sound perception in the normal hearing human including sound pressure generation in the ear canal, inertial forces of the middle ear ossicles, inertial forces acting on the cochlear fluid, alteration of the cochlear space, and sound pressure transmission from the skull interior [10]. The relative importance of these pathways has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Considered as the main medium of the sound wave vibration, the skull transmits the BC sound from the source to the cochlea. The inertia of the cochlear fluids and alteration of the bony shell surrounding the cochlea in human skulls are the most significant factors causing the BC hearing [8]. The transmission performance of the skull is affected by its anatomy, geometry, composition, and mechanical properties of the structures.…”
Section: Introductionmentioning
confidence: 99%